2022
DOI: 10.1002/ase.2155
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review: The use of augmented reality in clinical anatomical education and its assessment tools

Abstract: The need for sound anatomical knowledge is woven into the daily tasks of all health-care professionals, whether directly (e.g., surgical landmarks) or indirectly (e.g., understanding the pathophysiology of a disease) (Singh et al., 2015). Anatomy educators are searching for new, effective, and innovative means to teach medical trainees and professionals, beginning with two-dimensional (2D) images, plastic models, human cadavers, and, more recently, with the use of augmented reality (AR; Singh et al., 2015). Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 85 publications
(460 reference statements)
0
14
0
Order By: Relevance
“…Maniam et al successfully developed a MR tool incorporating the HoloLens and 3D printed models of temporal bones using Unity; however, they do not fully disclose their method for achieving object recognition and tracking [ 7 ]. Several review and scoping review articles reported the use of AR in anatomical education, but augmented objects included images and diagrams from books, as well as websites and cadavers, and varied between studies [ 24 , 25 , 26 ]. Our study used 3D printed personalised models derived from MRI data as augmented objects to develop a more advanced learning environment, but we only presented early findings on 3D printed models and image segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Maniam et al successfully developed a MR tool incorporating the HoloLens and 3D printed models of temporal bones using Unity; however, they do not fully disclose their method for achieving object recognition and tracking [ 7 ]. Several review and scoping review articles reported the use of AR in anatomical education, but augmented objects included images and diagrams from books, as well as websites and cadavers, and varied between studies [ 24 , 25 , 26 ]. Our study used 3D printed personalised models derived from MRI data as augmented objects to develop a more advanced learning environment, but we only presented early findings on 3D printed models and image segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of AR in academia suggests offering extraordinary experiences to students, by facilitating a friendlier environment and increasing attention (Adedokun-Shittu et al, 2020). Thus, students' attitude towards AR-based applications has been mostly evaluated in longitudinal design studies, where students indicated to be very happy by the use of this innovative learning methodology (McBain et al, 2022), which starts from the students' prior knowledge to favor the personalization of teaching (Soriano-Sánchez & Jiménez-Vázquez, 2023), guaranteeing the students' well-being (Requejo et al, 2022) and increasing their academic performance (Soriano-Sánchez & Jiménez-Vázquez, 2022a).…”
Section: Advantages Of Augmented Reality In Higher Educationmentioning
confidence: 99%
“…Likewise, the use of AR could strengthen the understanding of complex concepts, while supporting contextualization (Flores-Bascuñana et al, 2020). Likewise, a search has been conducted through ICT to respond to current educational needs, through an element that would be motivating for students and effective for teachers (Ayala et al, 2017;McBain et al, 2022). Thus, it has been observed how the realization of activities through the use of AR allows the development of adaptive capacity in front of any space, being a tool for approaching the imaginable and the unknown (Amaya & Santoyo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] In addition, the growing curricular volume of medical universities and reduction of hours dedicated to anatomy courses often requires less time-consuming teaching methods than dissection. 8,9 In parallel, computer-assisted learning (CAL) technologies, such as virtual reality (VR), [10][11][12][13] and augmented reality (AR), 14 three-dimensional (3D) models, [15][16][17] and interactive anatomical atlases [18][19][20] have rapidly advanced and grown in popularity. These resources became critical during the Covid-19 pandemic, when education activities were rapidly transferred to an e-learning format, due to decreased in person access to teaching resources.…”
Section: Introductionmentioning
confidence: 99%